Antigone - Sophocles (The Theban plays / by Sophocles, 1985)
A play performed by the British classical actors. Antigone is about the conflict between, moral and political law. The tale Oedipus and his family comes to an end- he himself his wife Jocasta, his sons and his daughter, all dead, Antigone is not the only victim in this play; Creon too comes to a tragic downfall-although he repents in time, bureacratic ritual results in the deaths of Creon's son and wife, burdening him with guilt as well as grief.